Perancangan Strategi Bisnis Dengan Pendekatan Blue Ocean Dalam Meningkatkan Penjualan (Studi Kasus: PD.Hj.Imat Cianjur) - Suyudi, Muhammad; Suryana, Hendy (Jurnal Media Teknik dan Sistem Industri, 2020)
Abstract— PD. Hj. Imat is a company engaged in the field of food one of the products it produces, namely sale pisang. The development of the current era the company decreased turnover because of the many competitors with the same food field one of them PD. Makmur. So at this time PD. Hj. Imat needs to make a strategy design that provides better future value. Therefore, this research is needed to find out what strategies are suitable for the company. After observing that the company is suitable to use the blue ocean strategy to solve the problems currently faced, the blue ocean strategy functions to design a strategy that focuses on creating new market space through an analysis of the strategy canvas while a four-step framework. The strategy canvas is used to determine the company's position against competitors in the market space. While this four-step framework functions to construct the attributes of the value of pe, buy and create a new curve. From the results of discussions that have been conducted by researchers, the strategy that needs to be applied in the future is to provide a new flavor variant, and the provision of labels on the packaging and the quality of the products must be more considered and improved in the future.Keywords: blue ocean strategy, value innovation, canvas strategy, four-step framework Abstrak— PD. Hj. Imat merupakan perusahaan yang bergerak di bidang makanan, salah satu produk yang dihasilkan yaitu sale pisang. Dengan berkembangnya jaman saat ini, perusahaan mengalami penurunan omset karena banyaknya pesaing dengan bidang makanan yang sama, salah satunya adalah PD. Makmur. Pada saat ini, PD. Hj. Imat perlu membuat rancangan strategi yang memberikan nilai lebih baik dengan menggunakan strategi blue ocean. Oleh karena itu, penelitian ini diperlukan untuk mengetahui strategi yang tepat bagi perusahaan dan dapat bertahan dalam persaingan serta sebagai alternative solusi dalam penyelesaian masalah perusahaan. Hasil pembahasan yang telah dilakukan oleh peneliti, maka strategi yang perlu diterapkan dalam pengembangan produk yaitu untuk memberikan varian rasa baru, pemberian label pada kemasan, dan kualitas produk harus lebih diperhatikan dan ditingkatkan.Kata kunci : strategi blue ocean, inovasi nilai, kanvas strategi, kerangka kerja empat langkah